CONSTRUCTING POLITICAL IMAGES THROUGH SOCIAL MEDIA: A VISUAL COMMUNICATION PERSPECTIVE - Garg, Anshul; Suri, Chanchal Sachdeva (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This is a narrative literature review that explores how social media can be used to construct political images through the visual communication, synthesizing 52 peer-reviewed materials (2008-2025). The political communication of the modern times is dominated by visual content, which includes images, videos, memes and triggers 3.2 times more interactions than text among 5.2 billion users. Such platforms as Instagram (1.8-3.2% engagement), X (memes), Tik Tok (youth mobilization), and Facebook (reach) facilitate algorithm-enhanced, personal image creation. Semiotics (polysemous signs) and visual framing/image-bite politics (emotional encoding) and political branding/personalization theories are all integrated as theoretical backgrounds. Examples of case studies include India 2024 (Modi: [?]6.61Cr visual adverts, 100M+ followers), US (Fetterman authenticity, Trump spectacle) elections, citing platform specific strategies and traits of cross-cultural behaviours. There are positive impacts such as voter mobilization (43 per cent vote influence India youth) and parasocial bonding and heuristic decision-making. The challenges regarding the negative issues include visual misinformation (18% deepfakes), polarization (X: +34%), and algorithm echo chambers. India-Western differences emphasize the cultural symbol potency (85% vs 60%).